2006
DOI: 10.1007/s00125-006-0239-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 11β-hydroxysteroid dehydrogenase type 1 reduces food intake and weight gain but maintains energy expenditure in diet-induced obese mice

Abstract: Aims/hypothesis: The 11β-hydroxysteroid dehydrogenase type-1 inhibitor BVT.2733 lowers blood glucose and insulin in mutant mouse models of obesity and diabetes. Its effects on energy balance and body composition, and their contribution to improved glucose homeostasis have received little attention. Materials and methods: BVT.2733 (100 mg/kg, orally) was given twice daily to lean and diet-induced obese mice for 16 or 17 days. A group of obese mice was pair-fed to the amounts consumed by BVT.2733-treated mice. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 10 publications
5
45
3
1
Order By: Relevance
“…Clarification of the potentially beneficial effects on (adipose and myocardial) angiogenesis will be needed. Central effects of 11 -HSD1 on appetite (Densmore et al, 2006) have been observed and some (Hermanowski-Vosatka 2005, Gu et al, 2005, Wang et al, 2006, but not all inhibitor studies report an effect on food intake. Since this appears to be weight loss, this could be a positive therapeutic effect.…”
Section: -Hsd1 Inhibitors As Therapeuticsmentioning
confidence: 99%
“…Clarification of the potentially beneficial effects on (adipose and myocardial) angiogenesis will be needed. Central effects of 11 -HSD1 on appetite (Densmore et al, 2006) have been observed and some (Hermanowski-Vosatka 2005, Gu et al, 2005, Wang et al, 2006, but not all inhibitor studies report an effect on food intake. Since this appears to be weight loss, this could be a positive therapeutic effect.…”
Section: -Hsd1 Inhibitors As Therapeuticsmentioning
confidence: 99%
“…It is noteworthy that ingestive behavior, a major confounding factor with regard to lipid metabolism, was not affected by low-dose CA as is the case in 11b-HSD1 -/-mice 9 or with higher doses of various inhibitors reported earlier. 10,11 This allowed assessment in this study of the direct, food intake-independent effects of 11b-HSD1 inhibition in the context of diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al, 2011;Morgan et al, 2009;Morgan & Tomlinson, 2010;Morton, 2010;Park et al, 2011;Rosenstock et al, 2010;U. Shah et al, 2010;Siu et al, 2009;Stewart & Tomlinson, 2009;Tiwari, 2010;Tu et al, 2008;van Raalte et al, 2009;Véniant et al, 2010;S. J. Wang et al, 2006;Webster et al, 2010;Yuan et al, 2007;X.…”
Section: β-Hsd1 Inhibition Studiesunclassified